The Impact of Skip vs. Non-Skip N2 Lymph Node Metastasis on the Prognosis of Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Wang, Xinxin; Guo, Haixie; Hu, Quanteng; Ying, Yongquan; Chen, Baofu (Frontiers in Surgery, 2021)
Objective: The skip N2 metastases were frequent in non-small-cell lung cancer (NSCLC) and the better prognosis of NSCLC with skip over non-skip N2 lymph node metastases is controversial. The primary aim of the present study is to investigate the prognosis effect of skip N2 lymph node metastases on survival of NSCLC. Setting: A literature search was conducted in PubMed, EMBASE and Cochrane Library with the term of (N2 OR (mediastinal lymph node) OR (mediastinal nodal metastases)) AND (lung cancer) AND (skip OR skipping) in the title/abstract field. The primary outcomes of interests are 3 and 5-year survival of NSCLC. Participants: Patients underwent complete resection by lobectomy, bilobectomy or pneumonectomy with systemic ipsilateral lymphadenectomy and were staged as pathologically N2 were included. Primary and secondary outcome measures: The 3 and 5-year survival of NSCLC was analysed. The impact of publication year, number of patients, baseline mean age, gender, histology, adjuvant therapy, number of skip N2 stations and survival analysis methods on the primary outcome were also analysed. Results: 21 of 409 studies with a total of 6806 patients met the inclusion criteria and were finally included for the analysis. The skip N2 lymph node metastases NSCLC had a significantly better OS than the non-skip N2 NSCLC (HR, 0.71; 95%CI, 0.62-0.82; P<0.001; I2=40.4%). The skip N2 lymph node metastases NSCLC had significantly higher 3 and 5-year survival rates than the non-skip N2 lymph node metastases NSCLC (OR, 0.75; 95%CI, 0.66-0.84; P<0.001; I2=60%; and OR, 0.78; 95%CI, 0.71-0.86; P<0.001; I2=67.1%, respectively). Conclusion: This meta-analysis suggests that the prognosis of skip N2 lymph node metastases NSCLC is better than that of non-skip N2 lymph node.